The Effect of Taxation Socialization, Understanding Taxation, Tax Rates, and Tax Sanction on Tax Compliance in Msme Padang City - Rindy Citra Dewi; Berta Agus Petra; Yamasitha Yamasitha; Anatia Agusti; Asri Juliani Br Tungkir (DINASTI RESEARCH, 2021)
This study aims to determine the effect of taxation socialization, understanding of taxation, tax rates, and tax sanctions on taxpayer compliance with UMKM in the city of Padang. This study used a population of the number of UMKM in North Padang Subdistrict and Nanggalo District, Padang City and 77 Samples obtained through purposive sampling method. The data used are primary data and the analytical method used is multiple regression.The results showed that Tax Socialization partially had a significant effect on Taxpayer Compliance, Tax Understanding partially had a significant effect on Taxpayer Compliance, Tax Rates partially had no significant effect on Taxpayer Compliance, Tax Sanctions partially had a significant effect on Taxpayer Compliance, whereas Tax Dissemination, Understanding of Taxes, Tax Rates, and Tax Sanctions simultaneously have a significant effect on Taxpayer Compliance.